CONCEPTUAL ASPECTS OF “FLEUR” IN FRENCH LITERATURE - Bozorova Dilnoza Shavkat qizi; Nazokatposho Axtamova Akmal qizi (Western European Studies, 2024)
This scientific article delves into the conceptual aspects of the term “Fleur” (flower) in French literature. “Fleur” holds multifaceted symbolic meanings and cultural significance, representing themes such as beauty, fragility, transience, renewal, and love in literary works. Through an analysis of selected literary texts, this study aims to explore the diverse conceptual dimensions of “Fleur” and its role in shaping narrative themes, character development, and cultural imagery in French literature
Keywords: chiphonéma; phytonyme; double articulation; mémorisation